Reminiscences of Michael Kelly, of the King's Theatre, and Theatre Royal Drury Lane, Volume 1 Including a Period of Nearly Half a Century - Kelly, Michael (Cambridge library collection. Music, 1826)
Michael Kelly (1762–1826) was an Irish singer and composer who studied music in a Naples conservatory before touring Europe and performing for royalty. His voyage to Italy began with a brush with pirates, one of whom was a childhood acquaintance. Kelly also found himself stranded penniless in Venice, spent a night in prison after a fist fight at the theatre, and had a narrow escape from revolutionary France. He is probably best remembered for creating the roles of Don Basilio and Don Curzio in the first performance, in 1786, of Le Nozze di Figaro, of which he describes the rehearsal period and reception. He later joined London's Theatre Royal as both a performer and composer and opened a music shop, which went bankrupt. These memoirs, published in 1826, provide rich first hand insights into a key period in theatre history. Volume 1 covers Kelly's early life and musical training